El ensayo periodístico - López Hidalgo, Antonio (Estudios sobre el Mensaje Periodístico, 2002)
The journalistic essay is a very slightly studied genre of opinion. Although its origin goes back to the prehistory of the journalism, it is not a genre in vogue nowadays. It appears and disappears from the pages of the magazines and of the specialized supplements and nobody knows for what deep reasons that happens this way. Today many authors consider it a modality of the journalistic article, even when it has its own characteristics to be considered as an autonomous genre. This article deals with some aspects of this genre with the intention to stimulate and intensify its study and it’s reading, because the essay is always a genre ready to be continuously renewing, even at less good times.